Do extended incubation recesses carry fitness costs in two cavity‐nesting birds?. Issue 2 (4th May 2017) - Bueno‐Enciso, Javier; Barrientos, Rafael; Ferrer, Esperanza S.; Sanz, Juan José
Abstract: Because extended incubation recesses, where incubating songbirds are away from nests for periods much longer than usual, occur infrequently, they have been treated as outliers in most previous studies and thus overlooked. However, egg temperatures can potentially fall below the physiological zero temperature during extended recesses, potentially affecting developing embryos. As such, evaluating extended recesses in an ecological context and identifying their possible fitness effects are important. With this aim, we used iButton data loggers to monitor the incubation behavior of female Blue Tits ( Cyanistes caeruleus ) and Great Tits ( Parus major ) during two breeding seasons in central Spain. We classified incubation recesses as extended if they were more than four times the mean recess duration for each species. Extended incubation recesses occurred more frequently in 2012 when females exhibited poorer body condition. Female Blue Tits had more extended incubation recesses than female Great Tits and, for both species, more extended recesses occurred at the beginning of the breeding season. Both nest attentiveness and average minimum nest temperature decreased when at least one extended recess occurred. Incubation periods averaged 4 d longer for nests where females had at least one extended recess, potentially increasing predation risk and resulting in lower‐quality nestlings. Overall, our results suggest that extended recesses may be more common among songbirds than previously thought and that, due to their effects on egg temperatures and attentiveness, they could impose fitness costs.